Implications of non-interest income on bank risk and performance of banks in selected developing and developed Asia Pacific countries - Koh, Chin Wei (2018)
This study was conducted to serve three main purposes which are: 1) to investigate bank specific and economic factors on bank non-interest based activities, 2) to investigate implications of non-interest income on bank risk and 3) to investigate implications of non-interest income on bank performance of banks in selected developing and developed Asia Pacific Countries. For the study on bank specific and economic factors on bank non-interest based activities in selected developing and developed Asia Pacific Countries over the years 2000-2015, we employ pooled OLS and panel regression to assess the bank specific and economic factors effect on bank non-interest based activities throughout 61 representative banks across Australia, Hong Kong, Korea, Malaysia, Singapore and Thailand in Asia Pacific region. The empirical findings indicate that the bank specific and economic factors do have impact on banks’ non-interest based activities in overall countries, developing and developed countries respectively. We also find that bank non-interest based activities also affected by subprime crisis for developed and developing countries. Furthermore, for the second objectives of the study, bank noninterest activities affect the bank risk in selected developing and developed Asia Pacific Countries. The empirical findings indicate that the bank non-interest based activities do have overall impact on Asia Pacific banks’ risk. Once we further study by segregating into developed and developing countries segment, we only able to find that the impact do significant on developing countries only not on developed countries. We also find that the bank risk do not affected by subprime crisis for Asia Pacific countries by factor in bank non-interest activities which indicate that non-interest activities provide risk shelter for banks in mitigating certain risks. For the third objective of the study, the empirical findings indicate that the bank non-interest based activities do have overall impact on Asia Pacific banks’ performance across overall, developing and developed countries but vary throughout bank performance proxies. This study suggested that with non-interest activities element, bank specific and economic factors have significant impacts on bank performance. We also find that the bank performance also affected by subprime crisis only for overall Asia Pacific countries especially developing countries but not developed countries by factor in bank non-interest activities. This study manages to achieve its objectives by providing evidence of the implications of bank specific and macroeconomic factor on bank non-interest activities in selected Asia Pacific countries. The findings of this study are expected to contribute significantly to new chapter of bank non-interest based activities of the Asia Pacific banking sector for bank regulators and investors.